Fatherhood dalam Surat Efesus 6:4 Sebagai Perspektif Baru tentang Peran Pengasuhan Ayah Terhadap Perkembangan Anak-Anak - Baskoro, Paulus Kunto; Dewantari, Shinta; Umboh, Steven Tommy Dalekes (Sekolah Tinggi Teologi Berea, Salatiga, 2023)
AbstractThe parenting pattern of fathers towards children is an important thing to understand and study seriously, because it is related to a generation. This understaning is called Fatherhood. The principles of parenting fathers to children, known as Fathergood, will be studied specifically through Ephesians 6:4. Paul in his letter discusses relationship in the family and specifically Paul advises fathers not to raise their children in anger that causes bitterness. Instead of educating children with the truth of God’s Word. So that the principles of Fatherhood can be implemented in the lives of believers today. The method used is descriptive literature method. This research will discuss about effective ways of evangelism, so that evangelism is more effective and can be applied in all ages. The Purpose of this writing is First, to find the principles of Fatherhood in Ephesians 6:4. Second, make every Chirstian family an example and pattern in educating children. Third, applying parenting patterns to children today. Keywords : Fatherhood, Role, Upbringing, Father, Son, Ephesus, Colossians AbstrakPola asuh ayah terhadap anak menjadi hal penting untuk dipahami dan dipelajari secara serius, sebab berhubungan dengan sebuah generasi. Pemahaman inilah yang disebut dengan Fatherhood. Prinsip-prinsip pola asuh ayah kepada anak yang dikenal dengan Fatherhood inilah yang akan dipelajari secara khusus lewat Surat Efesus 6:4. Paulus dalam suratnya membahas mengenai hubungan dalam keluarga dan secara khusus Paulus menasihatkan para ayah untuk tidak mendidik anak mereka dalam kemarahan yang menyebabkan kepahitan. Metode yang digunakan adalah metode deskriptif literatur. Penelitian ini akan membahas tentang cara yang efektif dalam penginjilan, sehingga penginjilan lebih tepat guna dapat diaplikasikan dalam segala zaman. Tujuan dalam penulisan ini adalah Pertama, menemukan prinsip-prinsip Fatherhood dalam Surat Efesus 6:4. Kedua, menjadikan setiap keluarga Kristen menjadi teladan dan pola dalam mendidik anak yang sesuai dengan kebenaran Firman Tuhan. Ketiga, mengaplikasikan pola asuh ayah kepada anak-anak pada masa kini. Kata-kata Kunci: Fatherhood, Peran, Asuh, Ayah, Anak, Efesus